(untitled) (Historia, 2021)
The Anglo-Boer War of 1899 to 1902 has over the years generated an enormous amount of interest, and up the end of 1998 at least 2 486 books, 2 002 journal articles and 889 pamphlets were published that dealt with the war as a whole, or with some aspect of the conflict, including the causes, the military course of events, the prisoners of war, the concentration camps, medical aspects, the role played by foreigners, and the peace negotiations. Books have been published on the role played by Canadians and Australians during the war, but the role of New Zealanders is less well-known, at least in South Africa. This gap has, to a large exte nt, been filled by the book by John Crawford (assisted by Ellen Ellis), To fight for the Empire: an illustrated history of New Zealand and the South African War, 1899-1902.